Efficacy and safety of sildenafil in Asian males with erectile dysfunction and cardiovascular risk - Peera Buranakitjaroen (2018)
Objective: Assess the effectiveness of sildenafil in Asian males with erectile dysfunction (ED) and one or more of the co-morbidities, mild-to-moderate hypertension, dyslipidemia, and diabetes. Material and Method: A six-week, double-blind, randomized, placebo-controlled, multicenter study was carried out in Thailand, Malaysia and Singapore One hundred and fifty five male subjects were randomized (2:1) to sildenafil (n = 104) or placebo (n = 51). Sildenafil was started at 50mg and increased (100 mg) or decreased (25mg) at week 2 if necessary. Results: On the primary efficacy endpoint, sildenafil-treated subjects had significantly better scores on the International Index of Erectile Function (IIEF) questions 3 and 4 than placebo (p < 0.001, both questions). When accumulated into IIEF domains, all five domains were significant in favor of sildenafil. In addition, sildenafil-treated subjects were more satisfied with treatment and had a higher intercourse success rate. The majority of adverse events were mild in severity; the most commonly reported treatment-related events were dizziness (7.7%) and tinnitus (2.9%). Conclusion: Sildenafil (25, 50, and 100 mg) was found to be an effective, safe, and well-tolerated treatment for ED in the present study population of Thai, Malaysian, and Singaporean males who also had increased cardiovascular risk.